The contribution of the Netherdutch Reformed Church of Africa (NHKA) to theological training at the Transvaal University College - Merwe, P. J. van der (HTS teologiese studies, 2008)
The ideal of theological training of candidates for the ministry of the Dutch Reformed Church (NHK) found its first (formal) expression in 1884. Difficult ecclesiastical, social and economic circumstances (including the consequences of the First and Second Anglo-Boer Wars) prevented dreams and plans from being realised. The opening of a Pretoria division of the Transvaal University College (TUC) in 1908 created new opportunities, but it would take another eight years before planning for theological training at the TUC could start. The NHK and the Presbyterian Church were involved as denominational partners in this undertaking. This phase lasted from 1917 to 1933. These humble beginnings laid the foundation for the theological training of ministers at university level – a paradigm which is still applicable in South Africa today.